Sinister grift [compact disc] - Panda Bear (Domino Recording Co., 2024)
On Panda Bear's first solo album in five years, he has returned with another statement that feels equally cumulative and unprecedented in his catalog. While his solo records have ranged from starkly intimate expressions of grief to colorful, electronic opuses, his music has never before sounded so warm and immediate. Working in his Lisbon, Portugal home studio with Animal Collective bandmate Josh "Deakin" Dibb, Lennox transforms Panda Bear into something resembling an old-school rock ensemble, playing nearly all the instruments himself and inviting kindred spirits into the process such as Cindy Lee, Spirit of the Beehive's Rivka Ravede, and, for the first time on a Panda Bear solo album, each of his Animal Collective bandmates.